(untitled) (The Journal of Interdisciplinary Human Studies, 2025)
This article explores the role of toys in fostering work ethic among preschool children. Work education at an early age is crucial for developing responsibility, persistence, and collaboration skills. Through structured and free play, toys serve as tools for teaching children the value of effort and cooperation. This study analyzes the types of toys that most effectively contribute to work-related behaviors and emphasizes the importance of age-appropriate, engaging, and educational toys. The findings suggest that a balanced approach combining guidance and independent exploration enhances the development of work habits in young children. The article also provides practical recommendations for parents and educators on selecting and using toys to foster early work ethic.